Ethnicity of the Hyksos Forces and the Death of Pharaoh Seqenenre Tao - Uroš Matić (Etnoantropološki Problemi)
The mummified remains of ancient Egyptian king Seqenenre Tao (c. 1560 BCE) reveal traces of trauma caused by violence. Several blows to his head produced cuts, allowing scholars to identify the weapons of the attackers. Considering that among these weapons were Levantine Middle Bronze Age II chisel-shaped, socketed axes, and that Middle Bronze Age II material culture is attributed to ‘Asiatics’ and the subjects of the 15th Dynasty (Hyksos), it is widely accepted that Seqenenre Tao died in conflict with the Hyksos forces. This paper analyses the culture-historical background behind this reasoning. Evidence for the use of weapons of foreign origin by the Egyptian forces is presented along with the possible mechanisms of their acquisition. The entanglement of weapons with the ethnic identity of their users is brought into question, allowing for several possible perpetrators and scenarios in which Seqenenre Tao died.